Akuntabilitas Pengelolaan Keuangan Masjid Di Kota Binjai, Studi Kasus Di Masjid (Al-Arif, Sabilal Muhtadin, Nurul Huda, Al-Istiqamah) - Alfin Hasan Ansari Ritonga; Hotbin Hasugian; Kusmilawaty Kusmilawaty (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study aims to determine how the accountability of mosque financial management. The mosques that became the researchers' objectives were the Al-Arif Mosque, the Sabilal Muhtadin Mosque, the Nurul Huda Mosque, the Al-Istiqomah Mosque in Binjai City. This research uses a qualitative approach method. The subjects in this study were BKM and mosque administrators and the object in this study was the mosque's financial statements. Data collection techniques are interviews, observation, and documentation. The data analysis technique used in this research is data reduction, data presentation, and conclusion drawing. From the results of research conducted by researchers, none of the mosques used PSAK 45 in the process of managing mosque finances, on average they were still manual and simple. Even though if you use accounting standards in management, the results obtained will be clearer and more detailed. Researchers suggest that the takmir of the Al-Arif Mosque, Sabilal Muhtadi Mosque, Nurul Huda Mosque and Al-Istiqamah Mosque should use PSAK 45 to be a guideline for accounting standards that have been implemented by the Indonesian accounting association contained in PSAK 45 so that the information presented is more relevant and has high comparability so that financial management in the future becomes better and more transparent in carrying out the mandate of the community.